2016
DOI: 10.1080/21655979.2016.1171437
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of L-phenylalanine to 2-phenylethanol by the novel stress-tolerant yeast Candida glycerinogenes WL2002-5

Abstract: 2-Phenylethanol (2-PE) is a high value aromatic alcohol with a rose-like odor that is utilized in the cosmetics and other industries. Although the chemical routes of 2-PE production have been altered by some microbial transformation processes, the poor tolerance to organic solvents of these microorganisms has limited the 2-PE yield. In this study, the stress-tolerant yeast Candida glycerinogenes WL2002-5 showed a 2-PE tolerance to 4 g/l, which is the highest reported to date. Moreover, the 2-PE titer in a batc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 31 publications
3
33
0
1
Order By: Relevance
“…In situ product removal, two-phase extraction and in situ product adsorption are used to alleviate the toxicity of 2-PE, which has been shown to be effective but uneconomical. Many efforts have been made to screen robust strains (Lu et al, 2016;Dai et al, 2020;Zhan et al, 2020). However, the molecular mechanism of 2-PE tolerance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In situ product removal, two-phase extraction and in situ product adsorption are used to alleviate the toxicity of 2-PE, which has been shown to be effective but uneconomical. Many efforts have been made to screen robust strains (Lu et al, 2016;Dai et al, 2020;Zhan et al, 2020). However, the molecular mechanism of 2-PE tolerance remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The microorganisms that are most efficient at producing 2-PE are yeasts, including S. cerevisiae, Kluyveromyces marxianus , Kluyveromyces lactis, Pichia fermentans , Candida glycerinogenes , and Z. rouxii ( Etschmann et al, 2003 ; Kim et al, 2014 ; Lu et al, 2016 ; Chreptowicz et al, 2018 ; Martínez-Avila et al, 2019 ). Yeasts are known to predominantly biosynthesize 2-PE via the Shikimate or Ehrlich pathways ( Figure 4 ) ( Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, De Lima et al (2018) evaluated the potential of yeast strain K. marxianus CCT 7735 in the 2-PE production and reported a production of 2.47 g/L of 2-PE, with the optimization in the medium through the optimal conditions achieving thus a production of 3.44 g/L of 2-PE. Lu et al (2016) showed the 2-PE titer in a batch fermentation with the stress-tolerant yeast Candida glycerinogenes WL2002-5, reaching 5 g/L from L-Phe, under optimized culture conditions. Genetic modification strategies have also been considered, to further increase 2-PE production, such as ARO8 and ARO10 overexpression in S. cerevisiae SPO810 yeast the 2-PE reached 2.61 g/L after 60 h of cultivation (Yin et al 2015).…”
Section: Production Of Volatile Organic Compoundsmentioning
confidence: 94%